2015
DOI: 10.1089/neu.2014.3640
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal DNA Methylation Profiling of Blast-Related Traumatic Brain Injury

Abstract: Long-term molecular changes in the brain resulting from blast exposure may be mediated by epigenetic changes, such as deoxyribonucleic acid (DNA) methylation, that regulate gene expression. Aberrant regulation of gene expression is associated with behavioral abnormalities, where DNA methylation bridges environmental signals to sustained changes in gene expression. We assessed DNA methylation changes in the brains of rats exposed to three 74.5 kPa blast overpressure events, conditions that have been associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 74 publications
(73 reference statements)
2
56
0
Order By: Relevance
“…Glial cell activation has been shown to be blast dependent where low level blasts lead to neuroprotective efforts and more severe exposures lead to inevitable cell death [8,12]. Changes in DNA methylation have been implicated in neuroinflammation [20,21]. Haghighi et al [20] found decreased global methylation patterns in glia cells relative to neurons following blast.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Glial cell activation has been shown to be blast dependent where low level blasts lead to neuroprotective efforts and more severe exposures lead to inevitable cell death [8,12]. Changes in DNA methylation have been implicated in neuroinflammation [20,21]. Haghighi et al [20] found decreased global methylation patterns in glia cells relative to neurons following blast.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in DNA methylation have been implicated in neuroinflammation [20,21]. Haghighi et al [20] found decreased global methylation patterns in glia cells relative to neurons following blast. Similarly, a subset of microglia/macrophages showed global decreases in DNA methylation levels following blunt TBI [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental traumatic brain injury (TBI) modifies the distribution and expression of Dnmt1, as well as DNA methylation at both the cellular and organ levels [72,73]. A recent study suggests that DNA hypomethylation and hypermethylation changes occur in both neurons and glia.…”
Section: Epigenetic Modifications Following Central Nervous System Inmentioning
confidence: 99%